2015
DOI: 10.1016/j.bonr.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Massive elimination of multinucleated osteoclasts by eupatilin is due to dual inhibition of transcription and cytoskeletal rearrangement

Abstract: Osteoporosis is an aging-associated disease requiring better therapeutic modality. Eupatilin is a major flavonoid from Artemisia plants such as Artemisia princeps and Artemisia argyi which has been reported to possess various beneficial biological effects including anti-inflammation, anti-tumor, anti-cancer, anti-allergy, and anti-oxidation activity. Complete blockade of RANK-dependent osteoclastogenesis was accomplished upon stimulation prior to the receptor activator of nuclear factor κB (RANK)-ligand (RANKL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…Taken together, these data suggest that eupatilin inhibits proliferation and drives morphological change in DHLFs by negatively regulating the transdifferentiation into myofibroblasts. In previous work, we demonstrated that eupatilin does not promote cell death [18]. Unexpectedly, our findings indicated that the HLEC/TGF-β axis does not contribute to IPF.…”
Section: Resultssupporting
confidence: 49%
See 2 more Smart Citations
“…Taken together, these data suggest that eupatilin inhibits proliferation and drives morphological change in DHLFs by negatively regulating the transdifferentiation into myofibroblasts. In previous work, we demonstrated that eupatilin does not promote cell death [18]. Unexpectedly, our findings indicated that the HLEC/TGF-β axis does not contribute to IPF.…”
Section: Resultssupporting
confidence: 49%
“…Formation of latent TGF-β complex loaded with processed active TGF-β, along with LTBP1 or LTBP4, integrin αvβ3 (or other integrin β family member), and LAP1, in the ECM is prerequisite for activation of TGFR [35]. Integrin αvβ3 is anchored to actin filaments at focal adhesions [36], and we showed previously that eupatilin has potent actin depolymerizing activity [18]. To explore the anti-fibrotic potential of eupatilin, we conducted a series of ICC experiments involving inhibition of actin depolymerization, which results in dismantling of the latent TGF-β complex.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, these data suggest that eupatilin inhibits proliferation and drives morphological change of DHLFs, thereby negatively regulating EMT. In previous work, we demonstrated that eupatilin does not promote cell death (10).…”
Section: Eupatilin Has Potent Anti-fibrogenic Capacitymentioning
confidence: 87%
“…10 Due to their anti-oxidant and anti-inflammatory activities, flavones have long been used to treat inflammatory diseases such as arthritis and asthma 11 Chromone, 1,4-benzopyrone-4-one, is a central chemical scaffold for flavones, 12 with chromone scaffoldcontaining derivatives (CSD) being a diverse family, with branching chemical residues coupled to this core chemical scaffold. 13 We recently reported that eupatilin, a CSD from an Artemisia species, dramatically inhibits lipopolysaccharide (LPS)-induced osteoporosis, partially via actin depolymerization 14 and the downregulation of multiple genes associated with the epithelial-mesenchymal transition (EMT). The present study shows that a noble CSD, ONG41008, can block the induction of Type 2 EMT, also called fibrogenesis, arrest cell growth and alter cell morphology, thereby substantially ameliorating lung fibrosis.…”
Section: Introductionmentioning
confidence: 99%